Malignant degeneration of perineal endometriosis in episiotomy scar, case report and review of the literature. Issue 3 (1st May 2007) - Chene, G.; Darcha, C.; Dechelotte, P.; Mage, G.; Canis, M.
Abstract : Although malignant degeneration of cutaneous endometriosis is rare at only 0.3–1% in endometriosis surgical scars, diagnosis and management need to be defined. A case of malignant degeneration of perineal endometriosis is reported, with a review of literature. Physiopathology, epidemiological data, diagnostic and therapeutic methods are discussed for malignant degeneration of cutaneous endometriosis. Any scar lesion that evolves in response to the menstrual cycle should be considered endometriosis until proven otherwise, and thus could require surgical resection, with histological analysis. A history of cutaneous endometriosis with frequent recurrences can indicate malignant degeneration. All cases require long-term clinical follow-up because, despite the rarity of this diagnosis, the delay between benign endometriosis and malignant transformation can vary from a few months to over 40 years.